2018
DOI: 10.1016/j.jcot.2018.07.008
|View full text |Cite|
|
Sign up to set email alerts
|

Meniscal repair and regeneration: Current strategies and future perspectives

Abstract: The management of meniscal injuries remains difficult and challenging. Although several clinical options exist for the treatment of such injuries, complete regeneration of the damaged meniscus has proved difficult due to the limited healing capacity of the tissue. With the advancements in tissue engineering and cell-based technologies, new therapeutic options for patients with currently incurable meniscal lesions now potentially exist. This review will discuss basic anatomy, current repair techniques and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 87 publications
1
42
0
3
Order By: Relevance
“…Experts were deciding to use bone marrow cells, biomaterials or autologous adipose tissue as meniscus repair methods. All of these approaches that involve the use of cells and biomaterial scaffolds have gained an increasing attention as potential regenerative therapies in the eld of musculoskeletal medicine very recently [4]. Therefore the observation than non-experts are less frequently choosing these options could be explained with their less experience with new therapeutic options for patients, as they still gain experience with traditional meniscus treatment methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experts were deciding to use bone marrow cells, biomaterials or autologous adipose tissue as meniscus repair methods. All of these approaches that involve the use of cells and biomaterial scaffolds have gained an increasing attention as potential regenerative therapies in the eld of musculoskeletal medicine very recently [4]. Therefore the observation than non-experts are less frequently choosing these options could be explained with their less experience with new therapeutic options for patients, as they still gain experience with traditional meniscus treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…The menisci injury is a common ailment of the knee injury [1]. Due to its hypovascularity and hypocellularity, a meniscus tear does not heal spontaneously [2,3,4] and prolonged untreated damage may lead to the development of osteoarthritis [5,6,7]. Current orthopedic practice aims to preserve meniscal integrity and restore its function [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Experts were deciding to use bone marrow cells, biomaterials or autologous adipose tissue as meniscus repair methods. All of these approaches that involve the use of cells and biomaterial scaffolds have recently gained increasing attention as potential regenerative therapies in the eld of musculoskeletal medicine [4]. Therefore, the observation that non-experts are less frequently choosing these options could be explained by their limited experience with new therapeutic options for patients, as they are still gaining experience with traditional meniscus treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Meniscus injuries represent a common ailment of knee damage [1]. Due to the hypovascularity and hypocellularity of the meniscus, meniscus tears do not heal spontaneously [2,3,4], and prolonged untreated damage may lead to the development of osteoarthritis [5,6,7]. Current orthopaedic practice aims to preserve meniscal integrity and restore function [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly more studies have suggested [15][16][17] that meniscus injury or defect will lead to an increase in the incidence of osteoarthritis, and thus meniscal repair has received increasingly more attention. Among the repair methods of meniscus injury [18] , meniscal suture repair is the mainstream repair method at present, and includes three types of repair: outside-in repair, inside-out repair and all-inside repair. Although the technique of inside-out repair is the gold standard for the treatment of the body and posterior angle of the meniscal tear, clinical studies have shown [19][20][21][22] that the clinical efficacy of all-inside repair is the same as that of inside-out repair, where all-inside repair has shorter operation time and fewer complications.…”
Section: Discussionmentioning
confidence: 99%